UNCTAD statistical pocketbook - United Nations; United Nations Conference on Trade and Development (New York : United Nations, 1984)
Provides essential background statistical information in a concise form on the varied issues addressed by UNCTAD in the field of trade and and development.
Latest issue consulted: 1994.
At head of title: United Nations Conference on Trade and Development.
oif 23/02/15
Ref
Keywords: Economic indicators; International trade; Balance of payments; Developing countries; Developing countries